A comparative study of efficacy of tadalafil and alfuzosin regimens in patients of benign prostate hyperplasia - Das, Supratik; Singh, Harjinder; Kumar, Vijay; Singh, Jasbir (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Aim of the study was to compare efficacy of Tadalafil and Alfuzosin regimens in patients of Benign Prostate Hyperplasia. Methods: It was a comparative, prospective, observational, non-invasive, parallel and randomised study conducted at the Outpatient Department of Urology, Rajindra Hospital, Patiala. 60 patients diagnosed with Benign Prostate Hyperplasia along with Lower Urinary Tract Symptoms, out which, 30 patients, consuming Tadalafil and 30 patients consuming Alfuzosin were considered. History regarding the concerned disease and the compliance of treatment was taken. Symptom scores were assessed with the help of International Prostate Symptom Score, Quality of Lifestyle Score and Erectile Dysfunction Score. Physical examination consisting of Focused Neurological Examination along with Digital Rectal Examination were conducted. Parameters like Renal Function Test, Urine analysis, Ultrasound of Prostate and uroflowmetry were also considered. Results: The mean age selected for study was 64 years for Tadalafil and Alfuzosin group. The mean level of IPS Score, Qol Score and ED Score at the first day of inclusion of patients were 23.96±4.49, 4±0.78, and 25.33±4.02 respectively for Tadalafil group and regarding Alfuzosin group they were 25.23±4.84, 3.56±0.81, and 26.1±4.04 respectively. Follow ups were conducted at 15 days, 1 month and 3 months for both the groups which were found to be statistically significant after 3 months and Alfuzosin showed a favourable result. Conclusions: Alfuzosin 10mg given at daily dose was found to have higher efficacy than Tadalafil (5mg).